Solvent-induced hearing loss from occupational exposure in Asia: a systematic review - Mohd Aris, Mohd Shukri; Zainal Abidin, Ainul Naqueah; Razali, Ailin; Ismail, Norazura; Fuente, Adrian (e-International Publishing House, Ltd., UK, 2021)
Exposure to certain solvents in the workplace can cause hearing loss. This study aims to bring attention to the existing literature on the adverse effects of solvents on workers' auditory function in a diverse occupational setting. The literature search used in this study is PubMed and Web of Science. 87% of the selected studies reported that the highest prevalence of hearing loss was from solvents and noise-exposed groups. Evidence shows that interaction between the solvent and the noise could be both additive and synergistic. More epidemiology studies on solvent-induced hearing loss using diverse approaches are warranted in the Asia region.